Reframing women’s empowerment in water security programmes in western Nepal - Leder, Stephanie; Clement, Floriane; Karki, Emma (Informa UK Limited, 2017)
Water security has become the new buzzword for water and development programmes in the rural South. The concept has potential to focus policymakers and practitioners on the inequalities and injustices that lie behind lack of access to affordable, safe, and clean water. The concept of women’s empowerment also provides an opportunity to do this. However, the vast majority of water security interventions using the term are apolitically and technically framed and fail to understand complex intersectional inequalities. We suspect that many of these interventions have been implemented following a business-as-usual approach with the risk of reproducing and even exacerbating existing gendered inequalities in access to and control over water. This article explores these concerns in the context of four villages in Western Nepal, where two internationally funded programmes aimed to empower women by improving access to water for both domestic and productive uses. They hoped to transform women into rural entrepreneurs and grassroots leaders. However, differences between women – such as age, marital status, caste, remittance flow, and land ownership – led to some women benefiting more than others. Water programmes must recognise and address difference between women if the poorest and most disadvantaged women are to benefit. Gender mainstreaming in the water sector needs to update its understanding of women’s empowerment in line with current feminist understandings of it as a processual, relational, and multi-dimensional concept. This means focusing on inter-household relations within communities, as well as intra-household relations. In addition, we recommend that water security programmes rely on more nuanced and context-specific understandings of women’s empowerment that go beyond enhanced access to resources and opportunities to develop agency to include social networks, critical consciousness, and values.